STATISTICAL ANALYSIS OF WORK ACCIDENTS IN SOYBEAN CULTIVATION, OCCURRED IN BRAZIL AND THE CENTRAL-WEST REGION, FROM 2008 TO 2018 - Mozena, A. L. K.; Mendes, N. A. C.; Santos, P. S. B. (Revista Brasileira de Engenharia de Biossistemas, 2020)
Soybean and its derived products are widely used for human and animal food worldwide. Brazil is the world's second largest producer of soybean and the largest supplier, with the Central-West region having the largest share of Brazilian production. In the country, the cultivation of soy is classified as an activity that comprises only the cultivation of the grain and the production of seeds, when this is complementary to the cultivation. Through data available in the Statistical Yearbook of Accidents at Work (Anuário Estatístico de Acidentes de Trabalho), work accidents occurred in Brazil and in the Central-West region during the period from 2008 to 2018 were analyzed. It was found that typical accidents were the most prevalent during the period (80.67%), showing an upward trend, and that the occurrences of accidents in the Central-West region significantly influence the national scenario. Non-tariff barriers imposed by customers for Brazilian soybean, which include the restriction of the use of certain chemicals for pest control, may contribute to reducing the incidence of occupational diseases. Programs aiming to improve health and safety in rural work, such as Soja Plus, which started in 2011, may influence the reduction of accidents without CAT (Work Accident Communication).